Rancang Bangun Kontrol Adaptif Suspensi Semi Aktif Seperempat Kendaraan Pada Damper Non Linier Melalui Metode Direct Response Frequency - Antonius Rajagukguk, (Teknika, 2008)
A suspension stability system will be increase if acceleration of mass vehicle decreases, so that need some control of suspension in order to isolate vibration of mass vehicle by condition of the road.In this thesis, it will discuss about regulator case of adaptive control design thru direct response frequency method for suspension control, with control design of model experiment of disturbance degree of 10 cm and response frequency of 1500 rad/sec, a mass vehicle degree can be decrease to 0.02 cm (0.2%) and vibration of oscillation of 1.5 seconds.